Canonical and non-canonical roles of oligodendrocyte precursor cells in mental disorders - Giulia Poggi; Giulia Treccani; Martina von der Bey; Arnaud Tanti; Michael J. Schmeisser; Marianne Müller (npj Mental Health Research)
Abstract Psychiatric research has shifted from a neuroncentric view to understanding mental disorders as disturbances of heterogeneous brain networks. Oligodendrocyte precursor cells (OPCs)— actively involved in the modulation of neuronal functions – are altered in psychiatric patients, but the extent and related consequences are unclear. This review explores canonical and non-canonical OPC-related pathways in schizophrenia, bipolar disorder, post-traumatic stress disorder, and depression in humans, highlighting potential mechanisms shared across diagnostic entities.